Assessment of the Role of Crop Rotation in Integrated Pest Management for Small-Scale Farmers - Mohamed, S. Peer (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
This article delves into the development and execution of integrated pest management (IPM) strategies for broadacre crop rotation in Tamil Nadu, India. It delves into global and Indian acceptance levels of IPM while recognizing variations due to method effectiveness, existing reliance on pesticide treatments, and a shortage of IPM advisors. Challenges in dealing with diverse pests are also acknowledged. The article discusses the collaborative efforts of farmers, agronomists, and entomologists in establishing and implementing IPM techniques for various products. Despite the absence of specific IPM techniques, the study reveals that there was enough information for Tamil Nadu's farmers to adopt IPM strategies. The article particularly assesses the role of crop rotation in IPM for small-scale farmers, focusing on practice transition and information sharing over entomological specifics.